The Role of Leadership and Organizational Culture in Achieving Business Excellence (Journal of Universal Excellence, 2026)
Research Question (RQ): How can visionary, inspiring and integrity-based leadership and an effective organizational culture contribute to increasing the performance and sustainable growth of organizations?Purpose: The purpose of the research is to investigate how various aspects of leadership and organizational culture influence the achievement of business excellence. The goal is to provide concrete findings and recommendations that will help organizations improve their performance through effective leadership approaches and culture.Method: To achieve the research objectives, we will use a qualitative approach that includes the analysis of examples of good practices in organizations, interviews with leaders and employees, and a review of existing literature. The theoretical framework is based on theories of leadership, emotional intelligence, and organizational culture, which enable an understanding of the connections between leadership and business excellence.Results: The expected results of the research show that successful leadership, based on a clear vision, integrity, and emotional intelligence, is key to creating an organizational culture that promotes innovation, collaboration, and long-term success. It will also be found that open communication and mutual respect contribute to greater motivation and productivity of employees.Organization: The research will have a direct impact on managers, as it will help them understand how they can achieve better business results through their leadership role and the creation of an appropriate organizational culture. The findings will enable leaders to develop strategies for better collaboration with employees and to achieve higher levels of innovation and competitiveness.Society: At the societal level, the research contributes to understanding how organizations, as part of the wider environment, can positively impact society. Incorporating values such as transparency, honesty and respect into leadership and organizational culture can contribute to greater corporate social responsibility and better working conditions and a better quality of life for employees.Originality: The originality of the research is demonstrated in the connection of the concepts of leadership and organizational culture with the achievement of business excellence in the modern business environment. The research offers a new perspective on how the integration of these two factors directly impacts the long-term success of organizations, allowing for a deeper understanding of leadership practices and their implications for business growth.Limitations/Future Research: Limitations of the research include the fact that it focuses on a specific context, which means that the results may not be fully transferable to all types of organizations. Further research could include a broader analysis of smaller companies and exploring the impact of digitalization on leadership and organizational culture.
Keywords: leadership; organizational culture; business excellence; emotional intelligence; strategic thinking; innovation; sustainable growth; open communication